ANALISIS PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN RETAIL TRADE YANG TERDAFTAR PADA BURSA EFEK INDONESIA TAHUN 2017-2019 - Marcella Tabita Langkun; Fransisca Rusgowanto (Universitas Logistik dan Bisnis Internasional, 2022)
This study aims to determine the effect of liquidity and solvency ratios on profitability. The variables tested in this study consisted of independent variables, namely liquidity and solvency, and the dependent variable was profitability. This type of research is quantitative research. The population in this study are all retail trading companies listed on the Indonesia Stock Exchange. The sample in this study amounted to 33 samples of retail trade companies used listed on the Indonesia Stock Exchange. The data analysis technique used is SPSS version 25, so the dependent variable (Y) Profitability has a minimum value of -0.11, a maximum value of 0.138. This variable has an average value of 0.03579 and a standard deviation of 0.041826. The independent variable (X1) Liquidity has a minimum value of 0.017, a maximum value of 2.801. This variable has an average value of 0.78994 and a standard deviation of 0.808678. The independent variable (X2) Solvency has a minimum value of 0.158, a maximum value of 0.884. This variable has an average value of 0.47158 and a standard deviation of 0.214967, with an Adjusted R Square value of 0.439. This shows that the value of the coefficient of determination from this study is 0.439 where this value explains 43.9% with the independent variable of this study being able to explain the dependent variable.